Police interaction and Notting Hill Carnival - Kilgallon, Ashley (Policing and society, 2020)
Discussions on public order policing often centre on the role of paramilitary policing tactics, only recently has the role of dialogue become more prominent within the field. This paper focuses on the latter, examining the interaction processes of Police Liaison Teams (PLTs) negotiating with revellers at Notting Hill Carnival. The PLTs are a newer tactical option within public order policing, they seek to act as a communicative bridge between different groups and the police. The PLTs were deployed at Notting Hill Carnival for the first time in 2016 charged with facilitating communication between the police and the Carnival floats - a performative feature of the event. Notting Hill Carnival attracts dense national and international crowds to the small urban location of Notting Hill in West London. Attended by approximately two million people every year it is the largest and most sensitive annual policing operation for the Metropolitan Police Service (MPS). The paper utilises data collected during fieldwork at Notting Hill Carnival over three consecutive years: 2015, 2016 and 2017. The paper draws from wider ethnographic research conducted between 2015 and 2017 with the public order unit at the MPS. Utilising the works of Goffman, this paper seeks to evidence how officers at Notting Hill Carnival operate within the confines of a professionally stigmatised identity. As such, the communicative foundations inherited by the PLTs are weak and unpredictable. Despite this, the paper also explores how PLT-reveller team-work is widely experienced, with both collaborating to ensure a positive Carnival experience.